COMPARATIVE CHARACTERISTICS OF CLINICAL FEATURES OF OCCUPATIONAL RESPIRATORY DISEASES TAKING INTO ACCOUNT BODY MASS INDEX AND OBESITY - Иващенко, Ирина Евгеньевна; Кузьменко, Марина Алексеевна; Алехно, Анастасия Сергеевна; Александрова, Ирина Вячеславовна; Карленко, Олеся Константиновна; Миллер, Ольга Юрьевна (Medicine in Kuzbass, 2025)
Chronic obstructive pulmonary disease (COPD) is one of the most common pathologies of the bronchopulmonary system, about 10-19% of COPD cases are associated with professional factors.The aim of the study was to study the course of professional COPD depending on the body mass index and obesity.Materials and methods. The case histories of patients (n = 206) with occupational COPD treated in the clinic of occupational pathology of the Novosibirsk Research Institute of Hygiene were analyzed. A comparative analysis of the course of OCOPD, complications and comorbid pathology in groups was carried out depending on the body mass index, the presence of abdominal-visceral obesity, which was determined by the waist/hip index and bioelectrical impedance. Statistical data processing was carried out using Excel spreadsheets and the Statistica-10.0 package.Results. The results of spirography, comparison of the number of complications and comorbid pathology in patients with different body mass index are presented. The greatest influence of the visceral type of obesity on the course of the disease in patients with occupational COPD is shown.The impedance method, in combination with the determination of the waist / hip index, allows you to identify disorders of the nutritional and metabolic status, diagnose the visceral type of obesity. Signs of obesity were identified by these methods in 112 subjects, when calculating the body mass index according to the Quetelet index, obesity was detected only in 84 patients.Conclusion. The course of occupational COPD depends on the body mass index and the presence of visceral obesity. To optimize therapy, reduce the severity of the disease, reduce the risk of mortality and improve the quality of life of patients, it is necessary to identify the visceral type of obesity in patients, for which the methods of determining the waist / hip index and bioimpedancemetry can be used.
Keywords: chronic obstructive pulmonary disease; visceral obesity; bioelectrical impedance; comorbid pathology